TECHNICAL BRIEF: Optimized pipeline for isolation of high-quality RNA from corneal cell subpopulations - Bath, Chris (Molecular Vision, 2014)
Purpose: Attempts to determine the transcriptional profile of discrete subsets of limbal epithelial cells in situ using laser capture microdissection (LCM) face two major challenges. First, the transcriptional profile of cells within a tissue may rapidly change as the tissue is excised and exposed to cold ischemia. Second, there is a risk of degradation of the RNA as the cellular compartment is separated from the remaining tissue. An optimized protocol for LCM of corneal epithelium is presented to address these issues. Methods: Experiments using porcine eye globes were carried out to determine both optimal procedures and settings for tissue harvest, transport, storage, histology, LCM, and RNA isolation. The optimized protocol was validated using human corneal epithelium. Results: To facilitate preservation of the gene expression profile, we have developed a mechanical tool for dissection of cornea that, in combination with flash freezing, enables tissue to be stored within 5 min of enucleation of the eye. Furthermore, we describe how RNA from limbal crypt cells may be obtained using a procedure involving cryosectioning, histological staining, and LCM. Conclusion: In this paper, we describe an optimized method for isolating high-quality RNA from cellular subpopulations confined to the limbal crypts of the cornea. The procedure yields RNA in amounts and quality suitable for downstream gene expression analyses, such as microarrays or next generation sequencing.